(untitled) (Third Sector Social Economic Review, 2025)
Sustainability has become a strategic priority that requires companies to go beyond profit-driven goals and integrate social, environmental, and economic responsibilities in a holistic manner. In this context, sustainable marketing practices contribute to the development of trust, loyalty, and a sense of belonging, particularly among internal stakeholders. This study examines how the economic sustainability practices carried out by ÇAYKUR, one of Turkey’s leading tea producers, are perceived by employees and how these perceptions influence brand image and brand trust. Data collected from 462 employees were analyzed using AMOS 22, SPSS 27.0, and Process Macro v4.3 software. The findings indicate that employees’ perceptions of economic sustainability positively affect the emotional brand image, and that this image significantly influences brand trust both directly and as a mediating variable. The results further demonstrate that when employees form an emotional connection with the brand, sustainability efforts become more effective in strengthening perceptions of brand trust. Thus, emotional engagement plays a crucial role in linking corporate sustainability initiatives to internal trust and brand credibility.